TEEN PREGNANCY AND THE USE OF CONTRACEPTIVE METHODS - Thelma Spindola; Nathalia da Silva Baptista Siqueira; Renata Lazone Cavalcanti (Revista de Pesquisa Cuidado é Fundamental Online)
Resumo Objetivos: Conhecer a percepção das gestantes adolescentes sobre emprego dos métodos contraceptivos; discutir a vivência das jovens relacionada à contracepção e práticas sexuais. Método: Pesquisa descritiva em abordagem qualitativa, com emprego da entrevista semi-estruturada e técnica de análise de conteúdo. Resultados: Participaram do estudo 17 gestantes adolescentes. Na análise temática das entrevistas emergiram quatro categorias: As adolescentes e adoção dos métodos contraceptivos; A contracepção na visão das gestantes adolescentes; As atividades educativas e a participação das jovens; Métodos Contraceptivos: dúvidas e incertezas das adolescentes. Conclusão: O estudo revela a vulnerabilidade das jovens para a ocorrência de uma gestação não planejada e o risco de uma reincidência. Acreditamos que as práticas educativas podem contribuir para o esclarecimento dos jovens acerca de sua sexualidade e práticas sexuais, prevenindo agravos na saúde sexual e reprodutiva. Abstract Goals: Perceptions of pregnant adolescents about employment of contraceptive methods; discuss the experience of young people regarding contraception and sexual practices. Method: Descriptive Research, qualitative approach, employment of content analysis technique and semi-structured interview. Results: Participated in the study 17 pregnant adolescents. The thematic analysis of interviews emerged four categories: The adolescent and adoption of contraception; contraception in vision of pregnant adolescents; educational activities and participation of young people; methods contraceptives: doubts and uncertainties of teenagers. Conclusion: The study highlights the vulnerability of youth to the occurrence of an unplanned pregnancy and the risk of a recurrence. We believe that educational practices can contribute to the understanding of young people about their sexuality and sexual practices, preventing injuries from sexual and reproductive health. Resumen